Proceedings of the 5th International Conference on the Durability of Concrete Structures 2016
DOI: 10.5703/1288284316147
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Effect of Steel Corrosion on the Bond–Slip Performance of Reinforced Concrete

Abstract: This paper studied the effects of reinforcement corrosion on bond performance between rebar and concrete. Tests were carried out to evaluate the degradation of bond between reinforcing steel and concrete for different corrosion levels of reinforcing steel. A series of 20 specimens of different concrete strength with various reinforcing steel corrosion levels were designed and manufactured. Each specimen was casted as a 200-mm concrete cube, and a steel rebar was centrally embedded with two stirrups around it. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Corrosion is the most frequent and relevant deterioration suffered by reinforced concrete structures, particularly in structures located in an aggressive marine environment [ 6 , 7 ]. Corrosion of reinforcement in the marine environment usually occurs because aggressive agents such as chloride ions are an electrochemical process [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corrosion is the most frequent and relevant deterioration suffered by reinforced concrete structures, particularly in structures located in an aggressive marine environment [ 6 , 7 ]. Corrosion of reinforcement in the marine environment usually occurs because aggressive agents such as chloride ions are an electrochemical process [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diverse research has been reported on the corrosion behavior of SCM and the structural, mechanical, chemical and structural properties [ 23 , 24 , 25 ]. The employ of SCM is an eco-friendly and cost-effective solution due to the natural properties of these materials [ 8 , 26 ]. An essential factor of SCM materials is their faster cure time in comparison with OPC.…”
Section: Introductionmentioning
confidence: 99%
“…Their lifes are less than 20 years in the harsh cold environment. [2] Although there are many advantages in prefabricated concrete structures, it is still restricted within many internal and external factors affected in the cold environment. We should use all reasonable ways to improve its durability.…”
Section: Introductionmentioning
confidence: 99%